Hemostasis, coagulation and thrombin in venoarterial and venovenous extracorporeal membrane oxygenation: the HECTIC study - Bruce Cartwright (Nature Portfolio, 2021)
Abstract Extracorporeal membrane oxygenation (ECMO) support has a high incidence of both bleeding and thrombotic complications. Despite clear differences in patient characteristics and pathologies between veno-venous (VV) and veno-arterial (VA) ECMO support, anticoagulation practices are often the same across modalities. Moreover, there is very little data on their respective coagulation profiles and comparisons of thrombin generation in these patients. This study compares the coagulation profile and thrombin generation between patients supported with either VV and VA ECMO. A prospective cohort study of patients undergoing VA and VV ECMO at an Intensive care department of a university hospital and ECMO referral centre. In addition to routine coagulation testing and heparin monitoring per unit protocol, thromboelastography (TEG), multiplate aggregometry (MEA), calibrated automated thrombinography (CAT) and von-Willebrand’s activity (antigen and activity ratio) were sampled second-daily for 1 week, then weekly thereafter. VA patients had significantly lower platelets counts, fibrinogen, anti-thrombin and clot strength with higher d-dimer levels than VV patients, consistent with a more pronounced consumptive coagulopathy. Thrombin generation was higher in VA than VV patients, and the heparin dose required to suppress thrombin generation was lower in VA patients. There were no significant differences in total bleeding or thrombotic event rates between VV and VA patients when adjusted for days on extracorporeal support. VA patients received a lower median daily heparin dose 8500 IU [IQR 2500–24000] versus VV 28,800 IU [IQR 17,300–40,800.00]; < 0.001. Twenty-eight patients (72%) survived to hospital discharge; comprising 53% of VA patients and 77% of VV patients. Significant differences between the coagulation profiles of VA and VV patients exist, and anticoagulation strategies for patients of these modalities should be different. Further research into the development of tailored anticoagulation strategies that include the mode of ECMO support need to be completed.